«Ed io che lasciai già l’ago e la gonna». Gender Issues in Laura Battiferri - Daniele (Lingüística y Literatura, 2022)
The article studies Laura Battiferri and analyzes some aspects of the poet’s life and literary path, such as her movements from Urbino to Rome and then to Florence, her presence in the Accademia degli Intronati, the role and the influence in the work of her husband, the sculptor Bartolomeo Ammannati, and the exchange of letters with Benedetto Varchi. In addition to her ability to fit and assert herself in the social and cultural context of her time, some of the themes that characterize the literary-academic debate of the Querelle des Femmes emerge clearly within her production.